2008
DOI: 10.1111/j.1526-4637.2008.00447.x
|View full text |Cite
|
Sign up to set email alerts
|

Pain Clinic Emergencies

Abstract: A B S T R A C TThe increasing recognition of the need to treat chronic pain has led to an increase in the number of interventional procedures performed on an outpatient basis, and consequently, a rise in the number of complications as well. Safe interventional pain management requires Pain specialists have a comprehensive understanding of how to perform a procedure as well as how to manage any acute complications. Though simplistic, an emphasis on prevention is the solution to avoiding a complication. This inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…In most cases, patients recover after conservative management such as cessation of the procedure, lying supine or in a Trendelenburg position, and administration of intravenous fluid and oxygen [42].…”
Section: Complications Associated With Interventional Therapiesmentioning
confidence: 98%
“…In most cases, patients recover after conservative management such as cessation of the procedure, lying supine or in a Trendelenburg position, and administration of intravenous fluid and oxygen [42].…”
Section: Complications Associated With Interventional Therapiesmentioning
confidence: 98%
“…First, it has been shown that patients with chronic pain conditions are more anxious at baseline and therefore may be at higher risk for procedural‐related anxiety than the general population [3,4]. Second, some complications specifically relating to anxiety, namely vasovagal reactions and intraprocedural hypertension, may be prevented through the use of anxiolytic medications [5‐7]. Third, studies have shown that certain patients prefer sedation for interventional pain procedures, especially when the option is discussed in detail prior to the procedure [8,9].…”
Section: Case Scenariomentioning
confidence: 99%
“…Specific complications relating to interventional pain management procedures may be related to periprocedural anxiety. A vasovagal reaction, which is a complex neurovascular reflex mediated by the autonomic nervous system, is the most frequent adverse event reported from interventional pain management procedures [5,6]. Stress, anxiety, fear, or pain associated with needle placement are the most common triggers, and preliminary warning signs include nausea, vomiting, diaphoresis, pallor, lightheadedness, disorientation, bradycardia, and generalized weakness.…”
Section: Case Scenariomentioning
confidence: 99%
See 2 more Smart Citations